1996
DOI: 10.1002/pc.10635
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thermal history on mechanical behavior of PEEK and its short‐fiber composites

Abstract: The effect of crystallinity differences induced by mold wall temperature and annealing on mechanical behavior is evaluated for poly(etheretherketone) (PEEK) resin and its composites. The systems investigated were neat PEEK, glass fiber (GF) reinforced PEEK, and carbon fiber (CF) reinforced PEEK. Both composite systems were reinforced with 10, 20, and 30 wt% fiber. The degree of crystallinity (Xc) of PEEK was found to increase by processing at higher mold temperatures, by annealing, and by fiber length reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…The presence of the glass beads had no significant influence on the crystallinity and the lamellar thickness of laser sintered PEK as shown in Table 1(a). Similarly, Sarasua et al, [32] found that increasing the glass fibre content of PEEK composites (from 10 to 30% GF) does not significantly affect the crystallinity. Table 1(a) presents the thermal expansion measurements of the injection moulded and high temperature laser sintered samples above and below the glass transition temperature as a function of the building direction.…”
Section: Ls-gb/pek Compositementioning
confidence: 99%
“…The presence of the glass beads had no significant influence on the crystallinity and the lamellar thickness of laser sintered PEK as shown in Table 1(a). Similarly, Sarasua et al, [32] found that increasing the glass fibre content of PEEK composites (from 10 to 30% GF) does not significantly affect the crystallinity. Table 1(a) presents the thermal expansion measurements of the injection moulded and high temperature laser sintered samples above and below the glass transition temperature as a function of the building direction.…”
Section: Ls-gb/pek Compositementioning
confidence: 99%
“…For example, in space applications, this material is sometimes employed as a replacement for aluminum because of its superior performance at high temperatures. To extend its structural applications, several studies have been devoted to enhance the properties of PEEK via incorporation of fillers such as glass fibers [20][21][22] and carbon fibers [23,24]. Recently, our group has demonstrated that the properties of this high-performance material can be significantly enhanced by the addition of single-walled carbon nanotubes (SWCNTs) [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the presence of carbon fillers (i.e., short fibers) changes the mechanical behavior irrespective of the crystallinity of the PEEK matrix. 22 The measurements here show that the amount of crystallinity (32%) is the same in the volume of beam and between the core and the outer surface of the beam. This is consistent with reports which showed that the presence of CNTs increases the crystallization temperature of PEEK but does not influence the crystallinity.…”
Section: A Tensile Strain Measurementsmentioning
confidence: 65%